2010
DOI: 10.1007/s11430-010-3076-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ocean tide loading displacements in Hong Kong using GPS technique

Abstract: Ocean tide loading (OTL) displacements of eight principal constituents at 12 sites in Hong Kong were determined using more than eight years of continuous GPS observations. Parameters of the OTL displacements were estimated using daily GPS solutions obtained with precise point positioning (PPP) technique. The results were compared with predictions from seven latest global ocean tide models. Gravity measurements of OTL in Hong Kong were also used to validate the GPS results. The study shows that the results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…NAO.99b model has high accuracy in Asia Pacific region [40]. Yuan et al point that when K1 and K2 are excluded from the statistics, the NAO99b model shows better agreement with the GPS OTL displacement estimates than the other models in Hong Kong [18], [41]. The residual between GNSS-derived OTLD parameters and model-derived OTLD parameters are listed in Appendix A and Appendix B.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…NAO.99b model has high accuracy in Asia Pacific region [40]. Yuan et al point that when K1 and K2 are excluded from the statistics, the NAO99b model shows better agreement with the GPS OTL displacement estimates than the other models in Hong Kong [18], [41]. The residual between GNSS-derived OTLD parameters and model-derived OTLD parameters are listed in Appendix A and Appendix B.…”
Section: Results and Analysismentioning
confidence: 99%
“…The harmonic analysis method is employed to estimate the OTLD parameters, which indicated that the estimation accuracy of each ocean tidal constituent is different [16], [17]. Yuan et al [18] compared the OTLD parameters estimated by GNSS with ocean tidal model prediction, and found that there are systematic deviations between GNSS-derived OTLD and tidal model prediction, and the estimation results of S2, K1 and K2 are not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic response of the solid earth to the redistribution of seawater mass caused by sea tides is often called the tidal load effect. In the offshore areas, the distortion caused by the tide loading effect can reach several centimeters (Yuan et al, 2010). Therefore, the impact of ocean tidal load must be taken into account in high precision geodetic research.…”
Section: Introductionmentioning
confidence: 99%
“…Greaves et al (Greaves et al .,2008) first conducted related research and they used the British GPS observation data to study the tide load, S2 and M2 results obtained from current GPS data and the FES99 model The difference is only 5%. Vergnolle (Vergnolle et al,2008) carried harmonic analysis by useing 14 GPS stations which located in northwestern france, found that the tide load correction differences between GPS inversion results and FES2004 model are 2~7mm, the amplitude difference of some tidal wave components is only sub-millimeter; Ito et al (Ito et al,2009) use Japan's dense GPS array and ultra guided gravimeter data extraction M2, found that the initial phase and amplitude given by global tide model and GPS observation are different.Yuan et al ( Yuan et al,2010) used several years of GPS data in Hong Kong calculating the eight major ocean tide components. A large number of continuous GPS tracking stations which located in the offshore area of China have been built up under many major projects, this provides us with an opportunity and possibility to refine Chinese local ocean tide model.…”
Section: Introductionmentioning
confidence: 99%
“…With accumulated continuous GPS (CGPS) observation data, it is now possible to comprehensively analyze the effect of the time series span on the establishment of the inferred noise model and thus on the likely velocities and their uncertainties (Langbein and Johnson, 1997;Zhu et al, 2003;Wang et al, 2005Wang et al, , 2008Cheng et al, 2008;Yang et al, 2008;Tian and Shen, 2009;Jiang and Liu, 2010;Yuan et al, 2010;Chen et al, 2012;Wang et al, 2013).…”
mentioning
confidence: 99%